2017
DOI: 10.4103/ija.ija_210_17
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative sildenafil therapy for children with ventricular septal defects and associated pulmonary hypertension undergoing corrective surgery: A randomised clinical trial

Abstract: Background and Aims:Sildenafil is known to reduce pulmonary artery pressure but its role in the perioperative period has not been well studied. We aimed to evaluate the efficacy of sildenafil in controlling post-operative pulmonary hypertension in children with pulmonary hypertension undergoing surgeries for correction of ventricular septal defect.Methods:The patients were divided randomly into two groups of thirty each. Group 1 (placebo) received pre-operative placebo and post-operative sildenafil (0.5mg/kg e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…(?)(? )Sidharth (2017)20 (−)( −) ( −) ( −) ( −) S. Al (2016) 21 (þ) ( þ) ( −) ( −) ( −) Vipul (2015) 22 (þ) ( þ) ( −) ( −) ( −) Yanliang (2014) 23 (−) ( −) ( −) ( −) ( −) I Palii (2014) 24 (−) ( −) ( −) ( −) ( −) Peiravian (2013) 25 (−) ( −) ( −) ( −) ( −) El Midanya (2013) 26 (−) ( −) ( −) ( −) ( −) A. Vassalos (2011) 27 (−) ( −) ( −) ( −) ( −) Sinan (2011) 28 (−) ( −) ( −) ( −) ( −) Alain (2010) 29 (−) ( −) ( −) ( −) ( −) Arturo (2010) 30 (−) ( −) ( −) ( −) ( −) Farah (2007) 31 (?) (?)…”
unclassified
“…(?)(? )Sidharth (2017)20 (−)( −) ( −) ( −) ( −) S. Al (2016) 21 (þ) ( þ) ( −) ( −) ( −) Vipul (2015) 22 (þ) ( þ) ( −) ( −) ( −) Yanliang (2014) 23 (−) ( −) ( −) ( −) ( −) I Palii (2014) 24 (−) ( −) ( −) ( −) ( −) Peiravian (2013) 25 (−) ( −) ( −) ( −) ( −) El Midanya (2013) 26 (−) ( −) ( −) ( −) ( −) A. Vassalos (2011) 27 (−) ( −) ( −) ( −) ( −) Sinan (2011) 28 (−) ( −) ( −) ( −) ( −) Alain (2010) 29 (−) ( −) ( −) ( −) ( −) Arturo (2010) 30 (−) ( −) ( −) ( −) ( −) Farah (2007) 31 (?) (?)…”
unclassified
“…Sildenafil is well tolerated in children with idiopathic pulmonary arterial hypertension [11]. The effects of sildenafil have reported in infants and children [12][13][14][15][16][17][18]. Sildenafil increases foetal body-weight at birth [12] and intravenous sildenafil improves oxygenation in infants [13].…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil reduces N-terminal pro b-type natriuretic peptide levels in all infants with bronchopulmonary dysplasia-associated pulmonary hypertension [16]. The use of perioperative sildenafil in children has a statistically significant reduction in the mean pulmonary artery pressure without any adverse-effects [17]. Intravenous sildenafil is as effective as inhaled nitric oxide and causes pulmonary vasodilator in children with congenital heart disease [18].…”
Section: Effects Of Sildenafil In Infants and Childrenmentioning
confidence: 99%
“…Only two of 44 studies described pre-operative/post-operative pharmacologic management of pulmonary artery hypertension beyond those which discuss intra-operative considerations. 18,19 One of these is the study by Ademir et al in 2013. These authors compared 282 infants (median age 5 months) based on age at the time of surgery: Group 1, age 0-3 months; Group 2, age 3-6 months; and Group 3, age 6-12 months.…”
Section: Pharmacologic Managementmentioning
confidence: 99%
“…Though the authors do not document the actual number of mortalities (if any), they do indicate that there was no mortality difference between the groups. 19 Unfortunately, there were no pulmonary vascular resistance indices reported, so these cannot be contrasted between groups. Nonetheless, this study demonstrated similar results of sildenafil to those of others with mixed groups of congenital heart lesions, though the long-term effects are unclear for all.…”
Section: Pharmacologic Managementmentioning
confidence: 99%